Impact of Anti-Citrullinated Protein Antibodies on Progressive Systemic Bone Mineral Density Loss in Patients With Early Rheumatoid Arthritis After Two Years of Treat-to-Target - Bugatti, Serena; Bogliolo, Laura; Manzo, Antonio; De Stefano, Ludovico; Delvino, Paolo; Motta, Francesca; Montecucco, Carlomaurizio (Frontiers in Immunology, 2021)
Objectives To investigate the association of anti-citrullinated protein antibodies (ACPA) with changes in systemic bone mineral density (BMD) in patients with early rheumatoid arthritis (RA) after two years of treat-to-target. Methods BMD was measured at the lumbar spine (LS) and femoral neck (FN) in 100 patients with recent onset RA at baseline and after 24 months of treatment aimed at low disease activity (LDA) according to the 28-joints disease activity score (DAS28 <3.2). Multivariable regression analyses were performed to determine independent associations between autoantibodies and other disease and treatment-related parameters with BMD loss. Results After 24 months, the majority of the patients were at least in LDA (78%), with slightly more ACPA-positive subjects achieving the target. The BMD had significantly decreased at both the LS (mean [SD] percent loss -1.8 [6.2], p=0.03) and the FN (-2.4 [7.3], p=0.03) in ACPA-positive but not in ACPA-negative patients. Consequently, the proportion of patients with reduced BMD (Z score ≤-1) after 24 months was significantly higher among ACPA-positive patients at both the spine (39.5% vs 19.3%, p=0.05) and the hip (37.2% vs 12.2%, p=0.007). The association between ACPA and BMD loss was independent of other variables including age, gender, disease activity, cumulative dose of glucocorticoids and duration of therapy with bisphosphonates at the LS but not the FN. Conclusions ACPA are associated with ongoing BMD loss at the spine despite suppression of inflammation and adoption of prophylactic measures. ACPA-positive RA patients should be therefore strictly monitored for the development of osteoporosis.